2013
DOI: 10.1152/ajpendo.00094.2013
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin acts through MT1/MT2 receptors to activate hypothalamic Akt and suppress hepatic gluconeogenesis in rats

Abstract: Melatonin can contribute to glucose homeostasis either by decreasing gluconeogenesis or by counteracting insulin resistance in distinct models of obesity. However, the precise mechanism through which melatonin controls glucose homeostasis is not completely understood. Male Wistar rats were administered an intracerebroventricular (icv) injection of melatonin and one of following: an icv injection of a phosphatidylinositol 3-kinase (PI3K) inhibitor, an icv injection of a melatonin receptor (MT) antagonist, or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 41 publications
(45 reference statements)
2
43
0
3
Order By: Relevance
“…Many studies have shown that melatonin has favorable effects on glucose homeostasis since it might increase glucose tolerance and improve insulin sensitivity in various animal models [32][33][34]. Melatonin administration has been shown to acutely decrease plasma insulin level and increase insulin sensitivity in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that melatonin has favorable effects on glucose homeostasis since it might increase glucose tolerance and improve insulin sensitivity in various animal models [32][33][34]. Melatonin administration has been shown to acutely decrease plasma insulin level and increase insulin sensitivity in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…This is because MT1/MT2 receptor signaling also reduces dyslipidemia, reduces hepatic glucose output, decreases adiposity and improves metabolic function. 41, 101, 102 Low melatonin levels have also been independently associated with T2DM risk. 103 Thus, stimulating melatonin signaling has been proposed as a treatment for metabolic syndrome.…”
Section: The Mt2 Receptor: Targeting Dysregulated Insulin Secretion Amentioning
confidence: 99%
“…103 Melatonin was shown to function by reducing hepatic gluconeogenesis and phosphorylation and activation of Akt in the hypothalamus. 101 Most of the recent research into the links between the melatonin receptors and diabetes is focused on MT2. Independent genome-wide association studies in European populations identified single nucleotide polymorphisms near MTNR1B that were associated with fasting plasma glucose, reduced beta cell function, and significantly increased T2DM risk: rs1387153 and rs10830963.…”
Section: The Mt2 Receptor: Targeting Dysregulated Insulin Secretion Amentioning
confidence: 99%
“…Melatonin has been shown to modulate the PI3K/Akt signaling pathway, which plays a central role in controlling cell growth, proliferation, survival, and differentiation (Faria et al, 2013;Lee et al, 2006;Proietti et al, 2011). Pharmacological doses of melatonin have been reported to induce Akt phosphorylation in mouse hippocampus, cultured primary astrocytes, and the ischemic rat brain (Kilic et al, 2005;Kong et al, 2008;Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%